Food security of paddy farm households based on the proportion of food expenditure and energy consumption level in Jogorogo Ngawi. Issue 1 (November 2021) - Larasati, A D P M; Darsono,; Marwanti, S
Abstract: Ngawi is the sixth paddy producer in Indonesia and certainly has an influence on the food security of paddy farm households. This study aimed to analyze the proportion of food expenditure (PFE), energy and protein consumption, the relationship between food expenditure and energy consumption, and the condition of food security. The basic method used descriptive analytic. The number of respondents based on the slovin formula was 87 households. The sample selection used stratified random sampling. The data analysis method used correlation with SPSS 22 and cross indicator between PFE and energy consumption level. The results showed that the average of PFE was 58.81%. The average energy consumption was 4, 272.2 kcal/household/day with an energy consumption level of 81.93% while the average protein consumption was 122.1 grams/household/day lower than the average household RDA consumption. Food expenditure had a significant relationship to energy consumption with a correlation coefficient of 0.925 including a very strong and unidirectional relationship. The contribution of household food security conditions were 28.7% secure; 32.2% vulnerable; 10.3% less secure; 28.8% insecure.